Fé e repressão política: atuação de militantes cristãos católicos sob a vigilância da Delegacia de Ordem Política e Social do Estado do Espírito Santo - DOPS/ES (1974-1985) - Silva, Erilaine Ribeiro da (2013)
This research propounds a study on the role of militant Catholic Christians in the State of Espirito Santo and the memories of repression from the files of the Bureau of Political and Social Order of Espírito Santo - (DOPS / ES) from the period of 1974 to 1985. In this context, sectors of the Church of Espírito Santo, with the Church of Brazil and Latin America, have emerged into political positions that generate distrust and fanfare on enforcement agencies responsible for the so-called "maintenance of order". The documents DOPS produced in order to identify the "enemies" of the regime, present to us the face of a political police that on behalf of State used to suppress all sources of opposition and, in this sense, attest monitoring suffered by Catholic Christians in the State. In other words, this research aims to identify the political activities of these militants and pastoral segments amid the backdrop of political openness characteristic initial period and intend to promote reflection on the role of these social activists as well as its contribution to the democratization of the country in the state of Espírito Santo.